Respons Agronomi dan Fisiologi Genotipe Padi (Oryza sativa L.) pada Budi Daya Berkelanjutan - Subarjo Subarjo; Dulbari Dulbari; Ratna Dewi (Jurnal Ilmu Pertanian Indonesia, 2024)
Efforts to maintain rice production in the future face many challenges, including the availability of increasingly narrow land, attacks by plant pest organisms, and declining land fertility due to improper cultivation systems. More than 70% of rice fields are in a disturbed ecological status due to cultivation technology that could be more environmentally friendly, which can interfere with the sustainability of rice self-sufficiency. An environmentally friendly rice cultivation system needs to be developed. This study aims to measure the agronomic and physiological responses of 3 rice genotypes in sustainable cultivation systems. The experiment used a Group Random Design on 3 rice genotypes (black, red, and white) in both conventional and sustainable cultivation systems. The research was carried out in the experimental garden of Polinela Organic Farm, Lampung State Polytechnic, from September 2020 to September 2021. The results showed that the plant, leaf greenery, number of tillers, number of panicles, grain weight per panicle, and biomass weight were not significantly different between conventional and sustainable cultivation. At the same time, the harvest and production indices per hectare were significantly different. The physiological responses to the photosynthesis and transpiration rates differed markedly in conventional and continuous cultivation. In contrast, the conductance of stomata did not differ significantly in both cultivation systems. The red rice genotype is the best, and it has a broader adaptation to conventional and sustainable cultivation systems. Keywords: agronomy, conventional sysem, physiology, rice genotype, sustainable system